2009
DOI: 10.1590/s1516-89132009000700023
|View full text |Cite
|
Sign up to set email alerts
|

A new alternative to produce gibberellic acid by solid state fermentation

Abstract: Gibberellic acid (GA 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
0
18
1
3
Order By: Relevance
“…It was observed that GA production initiated on the first day of fermentation, which is contrary to reports that GA commences about 46 h after the initiation of fermentation following nitrogen depletion in the medium (Escamilla et al, 2000;Rodrigues et al, 2009;Rios-Iribe et al, 2011). However, Lale and Gadre (2010) also reported GA production at 20 h by a mutant of G. fujikuroi.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…It was observed that GA production initiated on the first day of fermentation, which is contrary to reports that GA commences about 46 h after the initiation of fermentation following nitrogen depletion in the medium (Escamilla et al, 2000;Rodrigues et al, 2009;Rios-Iribe et al, 2011). However, Lale and Gadre (2010) also reported GA production at 20 h by a mutant of G. fujikuroi.…”
Section: Resultscontrasting
confidence: 74%
“…All these are relevant for a proper growth of the fermenting organisms and subsequent production of GA. Gibberellin production is reported to commence during the fermentation when nitrogen is exhausted in the medium and continues in the presence of adequate residual carbon in the substrate (Escamilla et al, 2000). Therefore, a good substrate should provide adequate nutrients for an initial mycelial growth in a nitrogen-limited but balanced medium (Rodrigues et al, 2009). The amount of carbohydrates (42.62%) and proteins (9.54%) recorded in the BP substrate fits the high C/N ratio recommended in substrates for GA production (Kumar and Lonsane, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, alguns estudos têm demonstrado aplicações sustentáveis para esses subprodutos, sendo empregados na produção de fertilizantes orgânicos, ração animal, produção de etanol, enzimas, óle-os essenciais e aditivos (Ferrari et al, 2004;Kobori & Jorge, 2005;Alexandrino, et al, 2007;Rodrigues et al, 2009;Tuttobene et al, 2009;Liu et al, 2010).…”
Section: Introductionunclassified
“…There are many economic benefits that are related to the discovery of potentially exploitable microorganisms in biotechnological processes, including the production of new therapeutic agents and antibiotics, probiotics, chemicals, enzymes and polymers for industrial applications Colwell, 1997;Hunter 1998;Angel, et al, 2000, Rodrigues, et al, 2009, Alberton et al, 2009, Sella et al, 2009. Microelements, also called trace elements, are present in small amounts in the body and are expressed in mg/kg or ppm (parts per million) of body weight (Ortolani, 2002).…”
Section: Introductionmentioning
confidence: 99%